2011
DOI: 10.1017/s0272263110000525
|View full text |Cite
|
Sign up to set email alerts
|

The Implicit Learning of Mappings Between Forms and Contextually Derived Meanings

Abstract: The traditional implicit learning literature has focused primarily on the abstraction of statistical regularities in form-form connections. More attention has been recently directed toward the implicit learning of form-meaning connections, which might be crucial in the acquisition of natural languages. The current article reports evidence for implicit learning of a mapping between a novel set of determiners and thematic roles, obtained using a newly developed reaction time methodology. The results conclude tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
124
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(134 citation statements)
references
References 45 publications
8
124
0
2
Order By: Relevance
“…All participants were native speakers of English. Following Leung & Williams (2011), we excluded individuals with advanced knowledge of a second language. None of the participants had ever studied Russian or any other Slavic language and none of them had any advanced knowledge of a language marking grammatical gender.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…All participants were native speakers of English. Following Leung & Williams (2011), we excluded individuals with advanced knowledge of a second language. None of the participants had ever studied Russian or any other Slavic language and none of them had any advanced knowledge of a language marking grammatical gender.…”
Section: Participantsmentioning
confidence: 99%
“…Therefore, when learning takes place via incidental exposure, there are grounds for thinking that animacy might be a significant contributor to the acquisition of grammatical knowledge: it is a salient feature of the input that can be attended to during learning without intention and explicit instruction. Previous research on implicit learning demonstrated that some learning is possible under incidental learning conditions (Lee, 2002;Leung & Williams, 2011;Rebuschat & Williams, 2012). However, it still remains unclear what factors contribute to the successful acquisition of a natural L2 grammar via incidental exposure.…”
Section: Introductionmentioning
confidence: 99%
“…L'impact de l'input dans les toutes premières étapes de l'acquisition d'une nouvelle langue est confi rmé par des travaux portant sur les langues artifi cielles (Leung et Williams, 2011), sur une période très brève (quelques minutes) d'exposition à l'input d'une langue naturelle (Gullberg et al ., 2012), ou encore sur le traitement de l'input d'une nouvelle langue lors des premières heures du cours d'initiation (Rast, 2008).…”
unclassified
“…Si certains travaux se sont intéressés à l'exposition initiale des apprenants à une nouvelle langue, soit ils ont utilisé une langue artifi cielle (voir Williams, 2005 ;Leung et Williams, 2011), soit ils se sont limités à l'analyse des performances des sujets après seulement quelques minutes d'accès à l'input (voir Zwitserlood et al ., 1994 ;Gullberg et al ., 2010Gullberg et al ., et 2012, sans la possibilité d'observer le développement et la consolidation des connaissances en langue cible après une exposition prolongée. Finalement, une étude menée par Rast (2008) permettant de suivre les toutes premières étapes d'acquisition sur une période plus longue (8 heures) a donné des résultats prometteurs.…”
unclassified
“…The theoretical and pedagogical significance of implicit learning in SLA has stimulated recent research interests (e.g. Leung & Williams, 2011;Robinson, 1996Robinson, , 2005Saffran, 2001;Saffran et al, 2008;Rebuschat & Williams, 2011). In the realm of L2 phonology, it has been shown that phonotactics (Dell, Reed, Adams, & Meyer, 2000;Onishi, Chambers, & Fisher, 2002;Warker & Dell, 2006), segmental features (Goldrick, 2004) and metrical stress rules (Gerken, 2004;Gerken & Bollt, 2008) may be learnt implicitly.…”
Section: Introductionmentioning
confidence: 99%